Penurunan Risiko pada Proses Impor di PT. X - Ellice Josephine Ongkodjojo; Felecia Felecia (Jurnal Titra, 2019)
PT. X is a multinational company that do a lot of export and import transactions. Import process that aren’t align with government’s regulations will be fined and so far, there are no prevention actions that conducted by the company for solving this problem. Reconcile method is a new way that is used for checking errors or mistakes that might be happened in import process especially in payment process. Later, data processing with reconcile method will be yield to category of risk potential that might be happened. Next, these categories will be assessed to determine the risk that is priority to be solved. Failure Mode Effects and Analysis (FMEA) will be used for assess the risk category. The objectives of this research are designing a risk, identify the root causes and propose some actions for solving the causes. The risk categories that have been discovered will be identified to know the root causes of its categories. The risk category that have the highest Risk Priority Number (RPN) will be prioritized to be solved. The top three categories with high RPN are different value, wrong freight calculation by customs broker and different quotation. Proposed solutions are used to minimize the risk potential of import process in the future and potentially reduce the fine by Rp 221.807.178,40. Proposed solutions in general are conduct standard communication with Asia procurement and socialization to workers from custom broker.